2007
DOI: 10.1093/pasj/59.sp1.s245
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Nickel Line Diagnostics for the Galactic Center Diffuse Emission

Abstract: We have observed the diffuse X-ray emission from the Galactic center (GC) using the X-ray Imaging Spectrometer (XIS) on Suzaku. The high-energy resolution and the low-background orbit provide excellent spectra of the GC diffuse X-rays (GCDX). The XIS found many emission lines in the GCDX near the energy of K-shell transitions of iron and nickel. The most pronounced features are Fe I Kα at 6.4 keV and K-shell absorption edge at 7.1 keV, which are from neutral and/or low ionization states of iron, and the K-shel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(57 citation statements)
references
References 36 publications
5
51
1
Order By: Relevance
“…SUZAKU observations [13] found also clear evidence for a hot plasma in the galactic central region with the diameter about 20 acrminutes (i.e ∼ 50 − 60 pc). Using the 6.9/6.7 keV ratio it was concluded that the spectrum in 5-11.5 keV range was naturally explained by a 6.5 keV-temperature plasma in collisional ionization equilibrium.…”
Section: Parameters Of X-ray Emission From the Galactic Centermentioning
confidence: 90%
See 2 more Smart Citations
“…SUZAKU observations [13] found also clear evidence for a hot plasma in the galactic central region with the diameter about 20 acrminutes (i.e ∼ 50 − 60 pc). Using the 6.9/6.7 keV ratio it was concluded that the spectrum in 5-11.5 keV range was naturally explained by a 6.5 keV-temperature plasma in collisional ionization equilibrium.…”
Section: Parameters Of X-ray Emission From the Galactic Centermentioning
confidence: 90%
“…Therefore, the origin of X-ray emission from there may be somewhat different from the rest of the Galaxy. Though observations shows there a significant contribution of discrete sources which apply from 20% to 40% of the total flux (see [11,12]), the SUZAKU data do not show correlation between the X-ray source distribution derived from Chandra data and the distribution of 6.7 keV line [13] that may contradict the source origin of hard X-ray emission from the Galactic center. Observations show also essential distinctions between X-ray emission from the Galactic ridge and from the Galactic center.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We compared the line energies that we obtain with NuSTAR to the results we obtained with Suzaku/XIS, which is an X-ray CCD camera with an accurate energy determination of ≲ 10 eV. 8 The observed spectra of NuSTAR and Suzaku/XIS in Figure 3 were individually fitted by a continuum model consisting of Energy (keV) Figure 3. Cas A spectra observed with (red) NuSTAR/FPMB and (black) Suzaku/XIS-3FI.…”
Section: Energy Scalementioning
confidence: 99%
“…This molecular gas occupies a rather small part of the central region, most of which is filled with a very hot gas. Recent SUZAKU measurements of the 6.9/6.7 keV iron line ratio [13] were naturally explained by a thermal emission of the 6.5 keV-temperature plasma. The plasma density was estimated in limits 0.1 − 0.2 cm −3 .…”
Section: Medium Properties In the Central Region Of The Galaxymentioning
confidence: 99%